EU policy objectives and energy investment decisions - Juan Alario (EIB Papers, 2007)
EU energy policies have changed focus in the last few years with a view to substantially reducing energy import dependency and greenhouse gas emissions. The EU Commission has played a leading role in defining the new orientations. The implementation of the EU policy objectives approved by the Council of March 2007 will require a substantial expansion of energy investments. However, the degree of uncertainty affecting investment decisions remains high, notably in relation to the pricing of CO2 and high energy-price volatility. To make the necessary investment in lowcarbon technologies happen, energy policies need to establish a credible long-term framework that reduces uncertainties.
Keywords: 330; EU-Energiepolitik; EU-Staaten